Relationship Between Values/ Worldview and Environmental Awareness: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This work attempts to clarify howenvironmental awareness can be utilised as a tool for environmental policymaking and management.  Since this studycovered various areas of social sciences  surrounding  the study  of  environmental awareness  and  its link  to behaviour, it was obligedto focus only on the key literatures in each area. Also, due to the informationconstraints, it was not able to obtain many of the original sources and often relied on the discussions in the tertiarysources. Despite of these limitations, this study hopes to demonstrate theimportance in considering environmental awareness as a new policy tool,additional to legal and economic instruments.